Editorial note: Welcome to the year 2024 and Volume 27 - Time for assisted kidney protection? - Assounga, Alain G (African Journal of Nephrology, 2024)
On behalf of the African Journal of Nephrology (AJN) editorial board, I wish all our contributors and readers a happy and prosperous new year. Welcome to 2024 and volume 27 of the Journal. The year 2023 was a pivotal one, in which the COVID-19 pandemic and its consequences receded. Some of the lessons learnt will continue to characterise our lives. We started the year with a very successful African Nephrology and Transplantation Summit in Cairo, a hybrid (in-person and virtual) congress. Continuing our progress, the AJN published four interesting reviews and 11 original articles, including one original in French. We thank all the contributors for selecting AJN to publish their valuable research findings. In 2019, we achieved becoming indexed in the Directory of Open Access Journals (DOAJ). This year, we are planning to apply for indexing by Scopus. The Journal will have to move to a professional hosting platform to sustain our progress. As this comes with additional costs, the editorial committee has decided that each publication will be charged a modest article processing fee of US$100. I invite all our future contributors to continue to support the Journal by submitting their best work. In particular, we wish to publish the best research on clinical nephrology in Africa. Special consideration will be given to manuscripts on tropical nephrology as the AJN wants to establish this as a niche topic. World Kidney Day 2024 will be celebrated on Thursday, 8 March. This year, the theme is “Kidney health for all – advancing equitable access to care and optimal medication practice”. As a young nephrology trainee, I was fascinated by home-based dialysis treatment for kidney failure. I still remember the 75-year-old patient who was successfully trained in two weeks to use a haemodialysis machine at home. There is much potential for home haemodialysis and this should be actively promoted. Of course, peritoneal dialysis is a well-established home-based therapy, which is already practised worldwide. The current data show that approximately 14–16% of the African population has chronic kidney disease (CKD) [1]. Africa, therefore, needs to manage at least one hundred million people with the condition. This is an impossibility using the current healthcare models. As most patients with early CKD stages are symptom-free, is it not time to screen everyone and train individuals to treat themselves? This may require that reno-protective medications be dispensed without a prescription by the pharmacist. CKD clinics might then be run in novel settings like sports clubs or gyms. The responsibility for protecting the kidney must be placed at an individual level, with clinics providing education and support. I propose the term “assisted kidney protection centre” to describe these clinics. We would accommodate the entire spectrum of clients, from individuals who need no assistance to those who require maximum assistance. Useful educational materials tailored to the public can be found in an earlier publication [2]. Making the knowledge, tools and support available to preserve kidney function through assisted kidney protection will contribute to advancing equitable access while providing individualised kidney care.